The Associations Between Service Quality, Corporate Image, Customer Satisfaction, and Loyalty: Evidence From the Malaysian Hotel Industry - Cheng, Boon Liat; Mansori, Shaheen; Cham, Tat Huei (Taylor & Francis Group, 2014)
Hotel operators strive to satisfy the needs of their guests and subse-quently retain them by trying to understand the factors that could build up a strong loyal clientele base. Previous studies have found that there are four critical perspectives related to the hotel indus-try that enable hotel operators to cope with the fierce competition in the industry and boost their profit margin: service quality, cus-tomer satisfaction, corporate image, and customer loyalty. This study attempts to evaluate the relationships between these perspec-tives. Systematic sampling approach was adopted in the study. The data was collected through self-administered questionnaires from 200 respondents. Statistical Package for the Social Sciences (SPSS) was used to test the hypothesized relationships in the research model. The findings reveal that the four variables are significantly related to one another and they are useful for hotel operators to promote long-term business growth and ensure sustainability in the hotel industry in Malaysia.